Cognitive Outcome of Infants with Pompe Disease Receiving Enzyme-Replacement Therapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at University Medical Center, Rotterdam, the Netherlands, and University of Leuven, Belgium prospectively assessed cognitive function in 10 children with classic infantile Pompe disease who had been treated with enzyme-replacement therapy (ERT) since 1999.